Total and Subtotal Aortic Replacement for Extensive Aortic Dissection in Patients with or without Marfan's Syndrome - Yamashita, Katsushi; Kazui, Teruhisa; Terada, Hitoshi; Washiyama, Naoki; Suzuki, Takayasu; Ohkura, Kazuhiro; Doi, Hirosato; Okawa, Yohei; Suzuki, Kazuchika; Ono, Takemi (General thoracic and cardiovascular surgery, 2002)
Extensive aortic dissection with multiple entries often found in Marfan's syndrome patients ultimately requires replacement of the whole aorta. We present a surgical strategy and results for total and subtotal aortic replacement. Subjects were 18 patients, including 14 Marfan's patients undergoing total (n = 13) or subtotal (excluding aortic arch) aortic replacement (n = 5), for DeBakey type I aortic dissection (n = 13) and DeBakey type IIIb aortic dissection with annuloaortic ectasia (n = 5) between February 1991 and April 2001. Mean age was 39.9 +/- 0.8 years--34.9 +/- 6.6 years in Marfan's patients vs. 57.7 +/- 4.7 years in non-Marfan patients. All operations were staged, with the mean number required per patient 3.1 +/- 0.8. Early mortality was 0% and late mortality 11% (2 of 18). Paraplegia or paraparesis occurring in 11%. Except for these patients, all current survivors enjoy good quality of life. Total and subtotal aortic replacement for extensive aortic dissection may decrease mortality due to rupture or associated disease.